FREQUENCY OF CEREBRAL VENOUS SINUS THROMBOSIS IN PATIENTS PRESENTED WITH HEADACHE AT HIGH ALTITUDE - Andaleeb Khan (Army Medical College Rawalpindi, 2019)
Objective: To determine the frequency of cerebral venous sinus thrombosis (CVST) among the patient with headache presenting from high altitude (HA). Study Design: Cross-sectional study.